2022
DOI: 10.1021/acsomega.2c01479
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Characteristics of Indonesian Oil Sand in a Fixed Bed

Abstract: In this research, pyrolysis experiment of Indonesian oil sand was performed in a fixed bed. Results show that the temperature and heating rate had significant effects on the pyrolysis products. Data studied include yields of products and the gaseous product composition of carbon monoxide, hydrogen, methane, and other hydrocarbons. Four functional group bands (aromatic hydrocarbon, oxygen, aliphatic, and hydroxyl functional groups) are observed from Fourier transform infrared spectroscopy of oil sand. The influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Notable observations showed that methane was the most dominant gas produced during the pyrolysis of oil sand bitumen, with Mile 2 bitumen exhibiting the highest methane yield (68.90%) and Orisunbare bitumen exhibiting the least methane yield (62.15%) among the bitumen samples. The high volume of methane gas generated during the pyrolysis of the Nigerian oil sand bitumen is consistent with the report of another study where methane gas was identified as the major gas component of Athabasca oil sand bitumen and Indonesian oil sand bitumen , after pyrolysis. Carbon (IV) oxide was next in product yield with 27.44, 23.90, and 31.47% for Agbabu, Mile 2, and Orisunbare bitumen, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Notable observations showed that methane was the most dominant gas produced during the pyrolysis of oil sand bitumen, with Mile 2 bitumen exhibiting the highest methane yield (68.90%) and Orisunbare bitumen exhibiting the least methane yield (62.15%) among the bitumen samples. The high volume of methane gas generated during the pyrolysis of the Nigerian oil sand bitumen is consistent with the report of another study where methane gas was identified as the major gas component of Athabasca oil sand bitumen and Indonesian oil sand bitumen , after pyrolysis. Carbon (IV) oxide was next in product yield with 27.44, 23.90, and 31.47% for Agbabu, Mile 2, and Orisunbare bitumen, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Many exciting studies have been carried out on estimating the pyrolysis kinetics of oil sands in recent years. Nevertheless, many of these studies have contributed significantly to the advances in knowledge with respect to the sole use of either model-free or model-fitting method as well as the proposition of mechanistic models of chemical structure evolution during the pyrolysis of the oil resource. However, the present study represents the first known attempt at evaluating the pyrolysis characteristics of Nigerian oil sands using model-free and model-fitting methods.…”
Section: Introductionmentioning
confidence: 99%